Critical and mainstream international business research: Making critical IB an integral part of a societally engaged international business discipline. Issue 2 (7th May 2019) - Dörrenbächer, Christoph; Gammelgaard, Jens
Abstract : Purpose: This paper aims to address the relationship between critical and mainstream international business (IB) research and discuss the ways forward for the former. Design/methodology/approach: The paper empirically maps critical IB scholarship by analysing more than 250 academic articles published in critical perspectives on international business ( cpoib ) from 2005 to 2017. The paper also includes a citation analysis that uncovers how critical IB research is recognized and discussed in mainstream IB studies. Findings: The extant critical IB research can be broken into five main topical clusters: positioning critical IB research, postcolonial IB studies, effects of international business activities, financialization and the global financial crisis and "Black IB" and corporate social responsibility. The citation analysis demonstrates that critical IB research is rarely recognized in mainstream IB academic outlets. Originality/value: This paper is the first to empirically map critical IB research and to measure its impact on mainstream IB research. Based on these insights, as well as discussions of the more critical voices within mainstream IB studies and the debate over critical performativity in critical management studies, ways of developing critical IB research are examined.